A new analytical method for the evaluation of cosmetic pigments. Issue 4 (26th January 2021) - Egurrola, Greciel; Segura, Juliette; García, Johnbrynner
Abstract: A new methodology is proposed for the instrumental evaluation of cosmetic pigments independent of their nature organic or inorganic, focusing on the assessment of its repeatability, reproducibility, and performance. This method involves the use of a silicone‐based dispersion medium that gives an optically clear film (YI = 0.90) and a dispersion procedure using a dual asymmetric centrifugal mixer aided with zirconium beads. Finally, a handheld spectrophotometer in a sphere d /8 spin configuration for the evaluation of the Spectral Reflectance Factor, L * a * b * C * h ° coordinates, tinting strength, and Δ E CMC colorimetric differences. Methodology shows a satisfactory repeatability, reproducibility, and an adequate correlation with the visual test, making this method a proper fit for quality control and meeting consumer color needs in the cosmetic industry.